The Determinants of Purchase Intention in Social Commerce - Sintia, Lydia; Siagian, Yolanda Masnita; Kurniawati, Kurniawati (Universitas Muhammadiyah Yogyakarta, 2023)
Research aims: The research aims to determine the determinants of purchase intention in social commerce.Design/Methodology/Approach: The population of this study was online shoppers. Questionnaires were distributed in Google Forms through various platforms. The sampling technique employed purposive sampling by drawing samples from 372 respondents. The data had been confirmed for their reliability and validity. The data analysis methods utilized were both quantitative and descriptive. Then, Structural Equation Modeling (SEM) was used for quantitative analysis.Research findings: The research uncovered that trust, attitude, and perceived usefulness significantly affected purchase intention. Then, the trust had a significant effect on attitude. Perceived ease of use also significantly affected subjective norms and perceived usefulness. However, this study highlights that subjective norms and alternative evaluations did not affect purchase intention.Theoretical contribution/Originality: This research enriches the reading of researchers on related subjects. Another contribution is that this research demonstrates that strengthening trust, attitude, and perceived usefulness in social commerce will increase purchase intention.Practitioner/Policy implication: This research will help other researchers, managers, investors, and government consider how social commerce opportunities can drive customer purchase intention. Research limitation/Implication: Since this research only discussed social media popular today, further research can discuss other developing social media. In addition, this study only discussed several variables affecting purchase intention. Hence, subsequent research can explain the role of artificial intelligence in encouraging purchase intention in social commerce.